Trajectories of Heart Activity Across Infancy to Early Childhood Differentially Predict Autism and Anxiety Symptoms in Fragile X Syndrome - Hogan, Abigail; Hunt, Erin; Smith, Kayla; Black, Conner; Bangert, Katherine; Klusek, Jessica; Roberts, Jane (Frontiers in Psychiatry, 2021)
Background: Fragile X syndrome (FXS) is characterized by high rates of autism spectrum disorder (ASD) and anxiety. The “hyperarousal hypothesis” in FXS has argued that autonomic nervous system (ANS) dysfunction underpins many symptoms of FXS. However, the developmental onset and trajectory of ANS dysfunction, as well as the consequences of ANS dysfunction on later psychiatric symptoms, remain poorly understood in FXS. This longitudinal study investigated whether and when males with FXS evidence atypical ANS function from infancy through early childhood, and how trajectories of ANS function across infancy and early childhood predict ASD and anxiety symptom severity later in development. Methods: Participants included 73 males with FXS and 79 age-matched typically developing (TD) males. Baseline heart activity was recorded at multiple assessments between 3 and 83 months of age, resulting in 372 observations. General arousal and parasympathetic activity were indexed via interbeat interval (IBI) and respiratory sinus arrhythmia (RSA), respectively. ASD and anxiety symptoms were assessed at 36 months of age or later in a subgroup of participants (FXS n=28; TD n=25). Results: Males with FXS exhibited less developmental change in ANS function across infancy and early childhood, with the FXS group exhibiting significantly shorter IBI and lower RSA by 29 and 24 months of age, respectively. Shorter IBI at 24 months and a flatter IBI slope across development predicted elevated anxiety symptoms, but not ASD symptoms, later in childhood in both FXS and TD males. Reduced RSA at 24 months predicted elevated ASD symptoms, but not anxiety symptoms, in both groups. Conclusion: Findings suggest that hyperarousal (i.e., shorter IBI, lower RSA) is evident in males with FXS by 24 to 29 months of age. General arousal, indexed by shorter IBI that becomes progressively more discrepant from TD controls, predicts later anxiety symptoms. In contrast, parasympathetic-related factors, indexed by lower levels of RSA, predict ASD symptoms. These findings support the “hyperarousal hypothesis” in FXS, in that ANS dysfunction evident early in development predicts later-emerging symptoms of ASD and anxiety. This study has important implications for the development of targeted treatments that could mitigate the long-term effects of hyperarousal in FXS.